Wygnańcy 1968 roku w świetle listów Felicji Bromberg, Anny Frajlich, Władysława Zająca .......... 373 - Wal, Anna (Tu jestem / zamieszkuję własne życie : studia i szkice o twórczości Anny Frajlich, 2018)
THE EXILES OF 1968 AS SEEN IN LETTERS BY FELICJA BROMBERG, ANNA FRAJLICH AND WŁADYSŁAW ZAJĄCThis article focuses on the correspondence of Felicja Bromberg, Anna Frajlich and Władysław Zając published under the title Po Marcu – Wiedeń, Rzym, Nowy Jork [‘After March – Vienna, Rome, New York’]. The authors of the letters left Poland in 1969 under the pressure of anti-Semitic propaganda after the events of March 1968. The letters to be found in this volume were addressed to Amalia and Psachie Frajlich, and written between November 1969 and June 1971. Despite its personal character, the correspondence is a valuable source of knowledge of the situation of the expatriates after 1968, their wandering across Europe and their settlement and acclimatization in New York. It is also an important source of biographical information for the critics of the literary works of Anna Frajlich, who is called the poet of exile.